ANXIETY RELATED TO ELDERLY SLEEP QUALITY - Zahroh, Chilyatiz; Masnia, Azizatul; Nadatien, Ima; Winoto, Priyo Mukti Pribadi (Universitas Nahdlatul Ulama Surabaya, 2021)
Background: Elderly face various health problems that need immediate and integrated handling. With increasing age, there will be a decrease in body function in the elderly both physically, physiologically and psychologically. The mental health problem that often occurs in the elderly is feeling worried. Objektif:: This study aims to analyze whether there is a relationship between anxiety levels and sleep quality among the elderly in Surabaya. Methods: The design of this study was analytic correlation with the approach used cross-sectional. The population Is all elderly in the qoryah thoyyibah kenjeran Surabaya posyandu, which amounted to 44 elderly. The sampel size of this study was 40 respondents, probability sampling technique was simple random sampling, this study contained an independent variable of anxiety level while the dependent variable was sleep quality. data collection instrument using a questionnaire. The data were analyzed using the spearman rank correlation test with a value of a = 0,05. Results: The results of research from 40 respondents showed that half (50%) experienced severe anxiety and almost half (47,5) had moderate sleep quality. Further analysis using the spearman rank test with a significance level of a= 0,05, the value of p=0.02 is obtained, which means p<a the Ho is rejected, which means that there is a relationship between the level of anxiety and the quality of sleep in the elderly at qoryah thoyyibah kenjeran Surabaya Conclusions: The conclusion of this study is that there is relationship between anxiety and sleep quality in the elderly at qoryah thoyyibah kenjeran Surabaya posyandu. It is hoped that the result of this study can develop the ability of further researchers to conduct more specific research related to the relationship between anxiety levels and sleep quality in the elderly.